User evaluation of a novel SMS-based reminder system for supporting post-stroke rehabilitation - Uno Fors; Julius T. Kamwesiga; Gunilla M. Eriksson; Lena von Koch; Susanne Guidetti (BMC Medical Informatics and Decision Making, 2019)
Abstract Background According to WHO stroke is a growing societal challenge and the third leading cause of global disease-burden estimated using disability-adjusted life years. Rehabilitation after stroke is an area of mutual interest for health care in many countries. Within the health care sector there is a growing emphasis on ICT services to provide clients with easier access to information, self-evaluation, and self-management. ICT-supported care programs possible to use in clients’ home environments are also recommended when there are long distances to the health care specialists. The aim of this study was to evaluate the technical usability of a SMS-based reminder system as well as user opinions when using such a system to assist clients to remember to perform daily rehabilitation activities, to rate their performance and to allow Occupational therapists (OT’s) to track and follow-up clients’ results over time. Methods Fifteen persons with stroke were invited to participate in the study and volunteered to receive daily SMS-based reminders regarding three activities to perform on a daily basis as well as answer daily SMS-based questions about their success rate during eight weeks. Clients, a number of family members, as well as OTs were interviewed to evaluate their opinions of using the reminder system. Results All clients were positive to the reminder system and felt that it helped them to regain their abilities. Their OTs agreed that the reminder and follow-up system was of benefit in the rehabilitation process. However, some technical and other issues were limiting the use of the system for some clients. The issues were mostly linked to the fact that the SMS system was based on a Swedish phone number, so that all messages needed to be sent internationally. Conclusion In conclusion, it seems that this type of SMS-based reminder systems could be of good use in the rehabilitation process after stroke, even in low income counties where few clients have access to Internet or smart phones, and where access to healthcare services is limited. However, since the results are based on clients’, OTs’ and family members’ expressed beliefs, we suggest that future research objectively investigate the intervention’s beneficial effects on the clients’ physical and cognitive health.